EFFECTS OF COMBAT SPORTS ON BONE MASS: SYSTEMATIC REVIEW - Barbeta,Camila Justino de Oliveira (2019)
ABSTRACT Objective To determine the influence of combat sports on bone mass. Methods A systematic review was performed according to the PRISMA method, with searches in the Pubmed, Bireme, Embase and Web of Science databases covering the period 1900 to 2015, using the keywords “martial arts”, “fight”, “combat”, “karate”, “kung fu”, “tae kwon do”, “judo”, “aikido”, “bone mass”, “bone health”, “bone tissue”, “bone density”, and “bone mineral contents”. The articles were searched for and retrieved electronically and manually, by two independent reviewers. Results Seventy-nine articles were identified, of which 25 were duplicates, leaving 54 for reading and evaluation of the titles; next, articles about diseases such as bone and/or orthopedic injuries, maxillofacial, surgeries, fractures, osteoporosis and osteopenia in women, prevention of falls, and physical fitness were excluded, leaving 15 articles. Of the articles selected and retrieved in full, all were published between 2002 and 2015. One article was a case control study; two were longitudinal studies, two were randomized studies; and 10 were cross-sectional studies. A total of 1368 children, adolescents, adults and elderly subjects were involved in combat sports and had bone evaluation by imaging. Factors such as calorie intake, calcium and/or vitamin D, intensity and volume of the exercise, hormonal aspects as bone markers, and characteristics of menopause are not conclusive in relation to bone mass, and further studies are needed. Conclusion The practice of combat sports shows a significant improvement in bone mass at all ages. Level of Evidence III, Therapeutic study – Investigation of treatment results.